A Guide to Femoral Arterial Access for Resuscitative Endovascular Balloon Occlusion of the Aorta - Nagashima, Futoshi; Kon, Yuri; Sugiyama, Takuya; Ishida, Kenichiro; Maruhashi, Takaaki; Matsumura, Yosuke (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Arterial access is essential in the resuscitation of trauma and hemorrhagic shock patients and can be effectively used for rapid endovascular treatment such as resuscitative endovascular balloon occlusion of the aorta (REBOA) and interventional radiology (IVR), continuous invasive hemodynamic monitoring, and frequent blood tests. In the REBOA procedure, obtaining arterial access is the first and most critical step. Arterial access can be obtained in three ways: (1) blind/landmark technique, (2) ultrasound-guided technique or (3) surgical cutdown technique. Regardless of which technique is chosen, it is crucial to recognize external landmarks before implementing any technique. In ultrasound-guided puncture, there are two types of techniques: short-axis puncture and long-axis puncture. There are two methods for actual puncture: the single-wall puncture method and the double-wall puncture method. In cases of hemorrhagic shock, the double-wall puncture method is advantageous when it is necessary to obtain arterial access quickly and reliably. The cutdown technique is useful when the femoral artery cannot be identified through ultrasound guidance or cannot be punctured for a long time owing to puncture-induced hematoma or obesity. This technique should be used without hesitation if it is evaluated to be more rapid and reliable than an ultrasound-guided puncture.